Making sense of the COVID-19 pandemic from the Bible – Some perspectives - Tolmie, D. F. (HTS teologiese studies, 2021)
In this article, a brief survey of some of the ways in which biblical scholars try to make sense of the coronavirus disease 2019 (COVID-19) pandemic is offered. The views of the following scholars are discussed: Walter Brueggemann, Ying Zhang, John Goldingay and Kathleen Scott Goldingay, N.T. Wright, Philemon M. Chamburuka and Ishanesu S. Gusha, and Peter Lampe. This is followed by the reflections of a biblical scholar and a systematic theologian. From the perspective of a biblical scholar, the following issues are raised: the richness of biblical traditions, the influence of social location on the interpretation of the pandemic in the light of the Bible, the importance of the emphasis on lament, the reluctance to interpret the pandemic as a punishment from God, the importance of the interpreter’s view of God and the emphasis on the way in which the ‘new normal’ should be approached. From the perspective of a systematic theologian the following issues are discussed: The nature of doing theology, the role of the symbol of the Divine, performativity of sense-making, the Trinitarian confession, an emerging new self and the importance of an ethic of responsibility.Contribution: The article is a response to the COVID-19 pandemic and emphasises the critical importance of engaging the Christian scripture. The role accorded to hermeneutics and to an explicit interdisciplinary conversation makes a particular contribution to the emerging crisis discourse.